Ethical Resilience as a Driver of Financial Performance and Social Impact: Toward a Composite Index for Public Value Sustainability in Arab Banking - Saad Zenad, Yaseer; Sami Hasab-Allah, Ahmad (Iraqi Journal for Administrative Sciences, 2026)
This study develops a composite index for Public Value Sustainability by integrating financial performance, ethical resilience, and social impact within Arab banking institutions. Moving beyond conventional financial metrics, the research conceptualizes ethical resilience as a structural driver that shapes both economic efficiency and societal contribution. Drawing on secondary data from governance, sustainability (ESG), and financial reports of Arab banks, the study employs confirmatory factor analysis and structural equation modelling to test a circular model that captures the dynamic interdependence among the three dimensions. The findings support a mutually reinforcing relationship in which ethical resilience enhances financial performance and social impact, while social impact, in turn, strengthens institutional ethical structures through increased legitimacy and public trust. This circular dynamic redefines sustainability as an integrated process rather than a linear outcome. The proposed composite index offers an original Arab framework for measuring ethical resilience as a foundational component of institutional sustainability. The study concludes that sustainable banking in the Arab context emerges when efficiency is aligned with justice and financial rationality is embedded within a coherent ethical architecture.